Consequences of obstetric fistula in sub Sahara African countries, from patients’ perspective: a systematic review of qualitative studies - Debrework Tesgera Bashah; Abebaw Gebeyehu Worku; Mezgebu Yitayal Mengistu (BMC Women's Health, 2018)
Abstract Background Women with fistula live in a state of distress and in fear of their future life. An obstetric fistula has a devastating impact on affected women and their families. The objective of this systematic review was to synthesize the evidence from published articles on the consequences of obstetric fistula on women who endure the condition. Methods The consequences were systematically reviewed from purely qualitative and mixed method primary studies. The literatures were searched through the search engines Google, Google scholar, Hinari using Pub Med data bases, and citation tracking. Relevant source of publications were searched for primary qualitative studies by formulating search protocol using related search terms. Time (articles published between January first of 2007 and 30th September 2016), participants (women who experienced obstetric fistula due to obstructed labor complications), types of study (purely qualitative and mixed method primary articles), findings (reporting consequences/impacts of obstetric fistula) were used as inclusion criteria. The quality appraisal tool for qualitative studies and the critical appraisal skills program were used to appraise the quality of the studies. The findings of sixteen studies were included in the review. The data were collected and then a thematic framework approach was applied for analysis. Results The thematic categories shared across most studies were related to the physical challenges of losing body control, women’s social and family relationships, and the challenges of losing income. Obstetric fistula has far reaching consequences on women’s physical well being, social and marital relationships, mental health and economic capacity. Fistula also challenged women coping abilities. Conclusion The consequences of obstetric fistula are far more than the visible medical condition. Little evidence is available on mental health, child and fertility issues, and coping mechanisms. Therefore, further researches shall be aimed at addressing the understudied area and suitable interventions shall be offered to improve women’s overall quality of life.